OP0182 Convergence of joint repair and pain pathways via nerve growth factor and p75 expressing mesenchymal stem cells- a novel explanation for osteoarthritis progression with anti-ngf in osteoarthritis. (15th June 2017) - Baboolal, T; Hinai, S Al; Jones, E; Reckless, J; Foster, M; Doyle, R; Forselles, K af; Westbrook, S; McGonagle, D
Abstract : Background: Nerve growth factor (NGF) is a key regulator of pain and anti-NGF therapy reduces osteoarthritis (OA) associated pain. However, anti-NGF therapy is associated with rapidly progressive OA (RPOA) [1]. In hip OA there is a 5-fold increase in mesenchymal stem cells (MSCs) from MRI bone marrow (BM) lesions, areas associated with OA progression [2]. MSCs in such lesions are uniformly positive for the NGF receptor, p75, which is also linked to chemotaxis and proliferation in other stromal cell compartments [3]. Objectives: Evaluate anti-NGF treatment in monoiodoacetate (MIA) induced OA and test whether NGF influences human BM-MSC function. Methods: Human tibial plateau (TP) bone was isolated from patients undergoing total knee replacement. OA was induced in male Wistar rats (n=6) by intra-articular injection of 0.3 mg MIA. Each animal was treated with subcutaneous injection of control human IgG or anti-NGF (3 mg/kg) at Days 5, 10 and 15. Human and animal tissues sections were prepared for histological analysis using H&E staining and immunohistochemistry (IHC) using anti-p75 and anti-NGF antibodies. BM-MSCs were isolated from iliac crest aspirates and cultured under normal conditions. Expression of p75 was induced following overnight incubation with 400mM ethanol (EtOH) and confirmed by flow cytometry. Proliferation was assessed ± EtOH and 0–1 μg/ml NGF. Results: Regions adjacent to cartilage loss in human TP showed abundant stromal proliferation, NGF and p75 immunoreactivity. In MIA model, by Day 18 there was substantial loss of cartilage, bone remodelling and stromal proliferation mimicking human disease. By Week 4 animals demonstrated unequal weight-bearing (p<0.05). Anti-NGF provided sufficient analgesia to normalise weight-bearing. Compared to IgG control, arthropathy progression was faster (Fig) with complete cartilage loss, bone marrow necrosis and cyst formation by Day 21. p75 immunoreactivity was greatly reduced in MIA-injected rats receiving anti-NGF compared with IgG. NGF positive staining was widespread in naïve and MIA-injected knees, but almost absent from MIA-treated knees of anti-NGF treated rats. To investigate increased p75 positivity in knee OA, we restored p75 expression loss in expanded cell, to 97% of BM-MSCs (n=3) using EtOH. Increased MSC proliferation was seen at Days 6 and 9 (26%, p=0.03 and 30%, p=0.01 increase respectively, n=7) for 1 μg/ml NGF in the presence of EtOH compared to control (no NGF). In cultures without EtOH induction (absent p75) NGF had no effect. Conclusions: TP bone from OA patients and rat MIA-treated subchondral bone contains p75 positive staining in regions of cartilage destruction and associated NGF positivity. Anti-NGF treatment exacerbated MIA-induced OA and reduced NGF and p75 expression. In vitro, NGF increased BM-MSC proliferation, suggesting NGF may be involved in the stromal proliferation seen at sites of OA damage. Thus, NGF may regulate MSC function. Complete blockade represents a novel mechanism for accelerated joint destruction in OA. References: Hochberg MC et al. Arthritis Rheumatol 2016. Campbell TM et al Arthritis Rheumatol 2016. Jiang Y, et al. Cartilag Arthritis Res Ther 2015. Disclosure of Interest: T. Baboolal: None declared, S. Al Hinai: None declared, E. Jones: None declared, J. Reckless Employee of: Rxcelerate Ltd, M. Foster Consultant for: Levicept Ltd, R. Doyle Employee of: Tetrad Discovery Ltd, K. af Forselles Consultant for: Levicept Ltd, S. Westbrook Shareholder of: Levicept Ltd, Employee of: Levicept Ltd, D. McGonagle: None declared